Organoleptic and Physicochemical Profile Comparison of Cow Milk Yogurt and 'Eggurt' Made from Different Egg Whites - Ridawati, Ridawati; Alsuhendra, Alsuhendra (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Yogurt is a widely consumed fermented dairy product known for its distinctive flavor, nutritional value, and health benefits. To expand its nutritional profile and enhance textural qualities, this study explores the use of egg whites as an alternative ingredient in yogurt production. The research compares the sensory and physicochemical properties of traditional milk yogurt with